2021
DOI: 10.3350/cmh.2020.0351
|View full text |Cite
|
Sign up to set email alerts
|

Serum milk fat globule-EGF factor 8 protein as a potential biomarker for metabolic syndrome

Abstract: Total number of figures and tables 3 figures and 3 tables List of Abbreviations HDL, high density lipoprotein; MFG-E8, milk fat globule-EGF factor-8; S-MAS, Seoul Metabolic Syndrome; BP, blood pressure; AUROC, area under the receiver operating characteristic curve; CI, confidence interval; OR, odds ratio; HR, hazard ratio; BMI, body mass index; LDL, low density lipoprotein; hsCRP, high sensitivity C-reactive protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“… 51 It has also been suggested that the reduced serum levels of MFGE-8 in patients with HCC or metabolic syndrome may serve as a diagnostic and prognostic biomarker. 52 , 53 Along these lines, hepatic expression of MFGE-8 is reduced in AHF patients, and the CCl 4 mouse model of AHF ( Figures 5 A and 5B) and MFGE-8 expression in liver pericytes correlates with angiogenesis in IRI. 54 Collectively, the aforementioned observations support a generalized protective role of MFGE-8 across several liver pathologies ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 79%
“… 51 It has also been suggested that the reduced serum levels of MFGE-8 in patients with HCC or metabolic syndrome may serve as a diagnostic and prognostic biomarker. 52 , 53 Along these lines, hepatic expression of MFGE-8 is reduced in AHF patients, and the CCl 4 mouse model of AHF ( Figures 5 A and 5B) and MFGE-8 expression in liver pericytes correlates with angiogenesis in IRI. 54 Collectively, the aforementioned observations support a generalized protective role of MFGE-8 across several liver pathologies ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 79%
“…Finally, among the 4 proteins of our fingerprint that were up-regulated in Cluster 1, Midkine and Lactadherin, were reported to be prominent during several chronic immune and metabolic disorders, such as atherosclerosis, cardiac, kidney and metabolic diseases [ 34 36 ]. Elevated levels of these proteins in Cluster 1 COPD patients are consistent with higher incidence of hypertension, diabetes and use of anti-hypertensive drugs and statins and they support the contribution of cardiometabolic co-morbidities to COPD severity [ 6 , 37 ].…”
Section: Discussionmentioning
confidence: 99%